2019 UK National Guideline for consultations requiring sexual history taking: Clinical Effectiveness Group British Association for Sexual Health and HIV. (September 2020) - Brook, G; Church, H; Evans, C; Jenkinson, N; McClean, H; Mohammed, H; Munro, H; Nambia, K; Saunders, J; Walton, L; Sullivan, A
This guideline is an update of a previous version published in 2013. In this new version, we have reflected changes in the way sexual health services are now provided by assuming an integrated Sexual Health/Sexual and Reproductive Healthcare service. There are new recommendations for online testing, female genital mutilation (FGM), chemsex and considerations for transgender (and non-binary) individuals. Previous versions rather assumed a cis-gender clientele and so we have taken a more mechanistic approach to sex and risk without assuming gender identification. We have updated our gender terminology in line with the British Association for Sexual Health and HIV 'sexual health standards for trans, including non-binary, people' although have retained the terminology of 'men' and 'women' in a few cases where it related to other guidelines, e.g. human papillomavirus vaccination and FGM.